Exploring Inclusive Education in Early Childhood: Perspectives, Practices, and Implementation - Deby Octaviany Ritonga; Junaidi Junaidi; Nurfaisal Nurfaisal (STAI Hubbulwathan Duri, 2025)
Inclusive education aims to provide equal learning opportunities for all children, including those with special needs. This study examines the perspectives and implementation of inclusive education at Taman Kanak-kanak (TK) Melati. A qualitative research design was employed, using a case study approach. Data were collected through interviews with teachers and parents, alongside observations of classroom practices. The findings indicate a strong commitment to inclusivity at TK Melati. Teachers apply differentiated instruction based on individual learning needs, utilize assistive technologies, and encourage social interaction through collaborative activities. Educators demonstrate enthusiasm and adapt teaching strategies to accommodate diverse learners. Additionally, collaboration with therapists and psychologists ensures tailored interventions for children with special needs, enhancing the effectiveness of support provided. While TK Melati exemplifies effective inclusive practices, the study highlights areas requiring improvement. Strengthening inclusive education calls for increased funding, targeted teacher training, and structured parental involvement. Furthermore, fostering strong partnerships between schools, families, and external professionals is essential for sustaining and enhancing inclusive practices.